Vibration analysis of three-screw pumps under pressure loads and rotor contact forces. (6th January 2016) - Li, Wanyou; Lu, Hanfeng; Zhang, Yue; Zhu, Chuan; Lu, Xiqun; Shuai, Zhijun
Abstract: Two main vibration sources in three-screw pumps, the fluid exciting force and the screw contact force, are studied to provide the basis for vibration control in this paper. A fluid exciting force model and a screw contact model are proposed to calculate these forces. An experimental test is carried out to obtain the vibration response of a three-screw pump. A calibrated finite element model of the three-screw pump is used to verify the vibration response under the fluid exciting force and the screw contact force obtained from the proposed models. The results show that the screw contact force is more dominant than the fluid exciting force. Highlights: Models of fluid force and screw contact force for a three-screw pump are developed. A simple and feasible load identification method by finite element method is devised to indirectly verify the force source. The vibration predictions from a calibrated finite element model are compared with test results. The contact force is found to be a dominant vibration source in a three-screw pump.